Numerical Optimization for Source-Drain Channel Resistance of AlGaN/GaN HEMTS - Yahyazadeh, Rajab; Hashempour , Zahra (Journal of Science and Technology, 2019)
A numerical model for the source-drain channel resistance based high electron mobility transistors has been developed that is capable to predict accurately the effects of polarization Coulomb Field Scattering (PCF), multi sub-band on source-drain channel resistance. Salient features of the model are incorporated of fully and partially occupied sub-bands in the interface quantum well, combined with a self-consistent solution of the Schrödinger and Poisson equations. In addition, to develop the model, accurate two-dimensional electron gas mobility and modified wave function in barrier AlGaN have been used. According to the numerical calculations, the effect of multi sub-band and PCF scattering on the increase of source-drain channel resistance is 35% and 65%, respectively, with the effect of PCF being almost twice as high as multi sub-band. The calculated model results are in very good agreement with existing experimental data for high electron mobility transistors device.